2011
DOI: 10.1074/jbc.m111.254797
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Integrin β Subunit Mutations That Alter Affinity for Extracellular Matrix Ligand

Abstract: We examined over 50 mutations in the Drosophila ␤PS integrin subunit that alter integrin function in situ for their ability to bind a soluble monovalent ligand, TWOW-1. Surprisingly, very few of the mutations, which were selected for conditional lethality in the fly, reduce the ligand binding ability of the integrin. The most prevalent class of mutations activates the integrin heterodimer. These findings emphasize the importance of integrin affinity regulation and point out how molecular interactions throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…Recently several point mutations in the extracellular domain of bPS integrin were identified that increase the affinity of aPS2bPS integrin binding to the extracellular matrix and cause lethality owing to this increase in affinity (Kendall et al, 2011). Lethality associated with some of these mutations can be suppressed by removing one copy of talin, confirming the role of talin as an integrin activator (Kendall et al, 2011).…”
Section: Mammalian Zasp Cooperates With Talin Head To Activate A5b1 Imentioning
confidence: 73%
See 4 more Smart Citations
“…Recently several point mutations in the extracellular domain of bPS integrin were identified that increase the affinity of aPS2bPS integrin binding to the extracellular matrix and cause lethality owing to this increase in affinity (Kendall et al, 2011). Lethality associated with some of these mutations can be suppressed by removing one copy of talin, confirming the role of talin as an integrin activator (Kendall et al, 2011).…”
Section: Mammalian Zasp Cooperates With Talin Head To Activate A5b1 Imentioning
confidence: 73%
“…We therefore tested the genetic interaction of two of these mutants (b44, I375F in the ADMIDAS and b30, I298F in b-I domain) with Zasp. Removing one copy of Zasp increases viability of b44 from 33% viable mutant males to 54%, n51445 [21% to 59% for rhea 2 (Drosophila talin) (Kendall et al, 2011)] and it increases viability of b30 from 41% to 57%, n51516 [3% to 44% for rhea 2 (Kendall et al, 2011)]. This suggests that both talin and Zasp are involved in modulating integrin affinity in Drosophila.…”
Section: Mammalian Zasp Cooperates With Talin Head To Activate A5b1 Imentioning
confidence: 90%
See 3 more Smart Citations